Trade in financial services, capital flows, and the value-at-risk of countries - Peter K. Cornelius (Deutsche Bank Research, 2000)
In light of the recent financial crises in the emerging markets, the coming-into-force of the financial services agreement under the GATS has been considered a success. While the agreement provides for little new liberalization but rather formalizes the status quo, it was feared that governments could even backtrack on previous commitments in the belief that more open markets could increase the degree of susceptibility by undermining financial stability. Strengthening the financial system's ability to evaluate and manage risk has therefore been identified as a precondition for more ambitious liberalization efforts in the future (Dobson and Jacquet, 1998). Encouragingly, in some countries banks have begun to implement Value-at-Risk approaches as a tool to assess their balance sheet vulnerability. As this paper argues, such an approach could also play a useful role in determining the extent of market risk on the macroeconomic level, with potentially important implications regarding trade in financial services, capital account convertibility, and international crisis management.
Keywords: F32; O16; 330; Financial crises; trade liberalization; capital flows; risk management; Internationaler Dienstleistungsverkehr; Finanzdienstleistung; Kapitalmobilität; WTO-Regeln; Außenhandelsliberalisierung; Risikomanagement; Welt; Finanzmarktkrise